Faktor Pendukung dan Penghambat Manajemen Kelas di TK Harapan Sindangsari - Panisa Dwi Julian; Elsa Ditha Fitria; Indah Maulidah; Widayanti Widayanti; Ayi Nurajijah; Enung Nuroniah; Sulastri Banyutresna (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
The education is very important in improving quality, because of that education improvements are carried out related to improving the teaching and learning process. Therefore, good classroom management is needed so that teaching and learning objectives canbe achieved. In classroom management, the teacher should pay attention to and create a classroom atmosphere so that it remains safe, comfortable and conducive. There are supporting and inhibiting factors in classroom management. This study aims to find out how the supporting and inhibiting factors of classroom management at Harapan Sindangsari Kindergarten are. This study used a qualitative approach with a descriptive research type. The techniques used in data collection are observation, interviews and document techniques. Data analysis uses inductive data analysis. The results of the study show that class management at Harapan Sindangsari Kindergarten has been going well but not optimally. Factors supporting classroom management come from facilities, teachers, principals, parents and students, inhibiting factors are challenges faced by teachers, how to handle children who need more attention, how to handle situations when many children are fussy, obstacles involving parents in the educational process of children in the kindergarten class